Knowledge, attitudes and practices regarding children with ICU-acquired weakness in pediatric intensive care unit among chinese medical staff: a cross-sectional survey - Di Huang; Weiwei Zhang; Weisi Peng; Yi Fan; Xin He; Ruirui Xing; XuDong Yan; Sijia Zhou; YueMing Peng; WeiXiang Luo (BMC, 2023)
Abstract Background ICU-AW (Intensive Care Unit Acquired Weakness) is characterized by significant muscle weakness and can be caused by a variety of factors, including immobility, medication use, and underlying medical conditions.ICU-AW can affect critically ill children who have been hospitalized in the PICU for an extended period of time.The knowledge, attitude and practice level of ICU-AW of PICU medical staff directly affect the treatment of critically ill children with ICU-AW.The aim to this study was to explore the knowledge, attitudes, and practices of Chinese medical staff regarding critically ill children with intensive care unit-acquired weakness (ICU-AW) and related factors. Methods A Knowledge, Attitudes, and Practices (KAP) Questionnaire regarding critically ill children with ICU-AW was distributed to a stratified sample of 530 pediatric intensive care unit (PICU) healthcare workers. The questionnaire consisted of 31 items-with scores of 45, 40, and 40 for each dimension and a total score of 125. Results The mean total score of Chinese PICU healthcare workers for the KAP questionnaire regarding children with ICU-AW was 87.36 ± 14.241 (53-121), with mean total knowledge, attitudes, and practices scores of 30.35 ± 6.317, 30.46 ± 5.632, and 26.54 ± 6.454, respectively. The population distribution indicated that 50.56%, 46.04%, and 3.4% of healthcare workers had poor, average, and good scores, respectively. Multiple linear regression showed that gender, education, and hospital level classification influenced the KAP level of PICU healthcare workers regarding critically ill children with ICU-AW. Conclusions Overall, PICU healthcare workers in China have an average KAP level about ICU-AW, and the gender and education level of PICU healthcare workers, as well as the classification of hospitals where they work, predict the KAP status of healthcare workers regarding children with ICU-AW. Therefore, healthcare leaders should plan and develop specific training programs to improve the KAP level of PICU healthcare workers.